A C‐terminal CXCL8 peptide based on chemokine–glycosaminoglycan interactions reduces neutrophil adhesion and migration during inflammation. Issue 2 (20th May 2019) - Martínez‐Burgo, Beatriz; Cobb, Steven L.; Pohl, Ehmke; Kashanin, Dmitry; Paul, Toby; Kirby, John A.; Sheerin, Neil S.; Ali, Simi
Summary: Leucocyte recruitment is critical during many acute and chronic inflammatory diseases. Chemokines are key mediators of leucocyte recruitment during the inflammatory response, by signalling through specific chemokine G‐protein‐coupled receptors (GPCRs). In addition, chemokines interact with cell‐surface glycosaminoglycans (GAGs) to generate a chemotactic gradient. The chemokine interleukin‐8/CXCL8, a prototypical neutrophil chemoattractant, is characterized by a long, highly positively charged GAG‐binding C‐terminal region, absent in most other chemokines. To examine whether the CXCL8 C‐terminal peptide has a modulatory role in GAG binding during neutrophil recruitment, we synthesized the wild‐type CXCL8 C‐terminal [CXCL8 (54–72)] (Peptide 1), a peptide with a substitution of glutamic acid (E) 70 with lysine (K) (Peptide 2) to increase positive charge; and also, a scrambled sequence peptide (Peptide 3). Surface plasmon resonance showed that Peptide 1, corresponding to the core CXCL8 GAG‐binding region, binds to GAG but Peptide 2 binding was detected at lower concentrations. In the absence of cellular GAG, the peptides did not affect CXCL8‐induced calcium signalling or neutrophil chemotaxis along a diffusion gradient, suggesting no effect on GPCR binding. All peptides equally inhibited neutrophil adhesion to endothelial cells under physiological flow conditions. Peptide 2, with its greater positive charge and binding to polyanionic GAG, inhibited CXCL8‐induced neutrophil transendothelial migration. Our studies suggest that the E70K CXCL8 peptide, may serve as a lead molecule for further development of therapeutic inhibitors of neutrophil‐mediated inflammation based on modulation of chemokine–GAG binding. Abstract : Martínez‐Burgo et al. describe the development of a C‐terminal CXCL8 peptide based on chemokine–glycosaminoglycan (GAG) interactions which reduces neutrophil adhesion and migration during inflammation. The model proposes the therapeutic potential of the peptide to modulate chemokine function by displacing chemokine from cell surface GAG potentially interfering with the formation of the chemokine gradient.